Characterization of the upper respiratory tract microbiota in Chilean asthmatic children reveals compositional, functional, and structural differences - Ignacio Ramos-Tapia; Katiuska L. Reynaldos-Grandón; Marcos Pérez-Losada; Eduardo Castro-Nallar; Eduardo Castro-Nallar (Frontiers in Allergy, 2023)
Around 155 million people worldwide suffer from asthma. In Chile, the prevalence of this disease in children is around 15% and has a high impact in the health system. Studies suggest that asthma is caused by multiple factors, including host genetics, antibiotic use, and the development of the airway microbiota. Here, we used 16S rRNA high-throughput sequencing to characterize the nasal and oral mucosae of 63 asthmatic and 89 healthy children (152 samples) from Santiago, Chile. We found that the nasal mucosa was dominated by a high abundance of Moraxella, Dolosigranulum, Haemophilus, Corynebacterium, Streptococcus, and Staphylococcus. In turn, the oral mucosa was characterized by a high abundance of Streptococcus, Haemophilus, Gemella, Veillonella, Neisseria, and Porphyromonas. Our results showed significantly (P < 0.001) lower alpha diversity and an over-abundance of Streptococcus (P < 0.01) in nasal samples from asthmatics compared to samples from healthy subjects. Community structure, as revealed by co-occurrence networks, showed different microbial interactions in asthmatic and healthy subjects, particularly in the nasal microbiota. The networks revealed keystone genera in each body site, including Prevotella, Leptotrichia, and Porphyromonas in the nasal microbiota, and Streptococcus, Granulicatella, and Veillonella in the oral microbiota. We also detected 51 functional pathways differentially abundant on the nasal mucosa of asthmatic subjects, although only 13 pathways were overrepresented in the asthmatic subjects (P < 0.05). We did not find any significant differences in microbial taxonomic (composition and structure) and functional diversity between the oral mucosa of asthmatic and healthy subjects. This study explores for the first time the relationships between the upper respiratory airways bacteriome and asthma in Chile. It demonstrates that the nasal cavity of children from Santiago harbors unique bacterial communities and identifies potential taxonomic and functional biomarkers of pediatric asthma.